Phase relations near ternary eutectic point in the Ag-In-Sb system - Jendrzejczyk-Handzlik D.; Živković Dragana; Gierlotka W.; Manasijević D.; Fitzner K.; Minić D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The results of the phase relations near ternary eutectic point in the Ag-In-Sb system are investigated in this paper. Phase equilibrium calculation was done using Thermocalc software and experimental DTA results for the chosen alloys in the isopleths with molar ration of In:Sb = 7:3; 9:1 and 1:1. The structural characteristics of these alloys have been investigated using light optic microscopy and scanning electron microscopy, while hardness measurements have also been done. Solidification path for three ternary alloys located on three different investigated isopleths was calculated using Pandat software.